Development of arc-laminated bamboo lumber - Jimenez, Juanito P., Jr.; Narividad, Robert A. (2019)
This study was conducted to develop arc-laminated bamboo lumber (ALBL) from bamboo splits using middle portions of the culms of Kauayan-tinik (Bambusa blumeana Schult.f.) and Bolo [Gigantochloa levis (Blanco) Merr.]. Arc lamination of quarter split culm was employed instead of the rectangular machined bamboo slats. Polyvinyl acetate (PVAc) and polyurethane (PUR) adhesives with glue spreads of 80, 120, and 160 g/m² were used. Mechanical press with an arc mold was used in the lamination. Conditioned laminated samples were tested following ASTM and PNS procedures. In general, the arc-laminated B. blumeana had better physical properties than G. levis as shown by the former’s lower radial and tangential swelling in both PVAc and PUR adhesives regardless of glue spread. The mechanical properties and delamination tests showed that best glue spread is 80 g/m² for both bamboo species. This implies that glue spread can be lowered up to 80 g/m² for ALBL to reduce glue consumption.
Keywords: Bamboo; Bamboo products